Genotypic yield responses of lowland rice in high‐altitude cropping systems - Razafindrazaka, A.; Stuerz, S.; Cotter, M.; Rajaona, A.; Asch, F. (Wiley, 2020)
Rising global mean temperatures open opportunities in high‐altitude production systems for temperature‐sensitive crops such as lowland rice. Currently, the cropping window for rice in higher altitudes is still narrow, and thus, genotypes that tolerate a certain degree of chilling are needed to achieve their potential yield. Final yield depends on the interaction between genotype and environmental conditions. Exposing the genotype to a wide range of environments is a way to evaluate its adaptability into an expanding cropping calendar. Over a 2‐year period, an experiment was conducted in lowland rice systems in Madagascar at two locations differing in altitude. Twenty genotypes with contrasting levels of tolerance to low temperature were sown monthly in a non‐replicated rice garden trial. Plant development was monitored and yield and yield components were determined. Yield stability across the different growing environments was investigated. While crop duration was affected by sowing dates and altitude, yield was mainly determined by sowing date. Panicle number per m2 and number of spikelets per panicle were the most limiting factors for yield potential in mid‐altitude, while in high altitude, yield was mainly limited by spikelet fertility. Resulting cropping calendar and genotype recommendations are discussed.